Study on Fractional Differential Equations via Atangana-Baleanu Fractional Derivative - Harikrishnan, S.; Kanagarajan, K.; Vivek, D. (Journal of Vibration Testing and System Dynamics, 2026)
In this note, we establish the existence, uniqueness and stability of a special class of fractional pantograph equation with Atangana- Baleanu fractional derivative(ABFD). The arguments are based upon Schauder fixed point theorem and Banach contraction principle. In addition, we discuss the stability results of proposed equation by the concept of Ulam. At last an example is given to illustrate the theory.